Discussions around the spatial dimension in the social sciences. A contribution from Geography and Sociology - Carlos Hugo Soria Caceres (Geografares, 2022)
This research aims to reflect the difficulties that Geography and Sociology have presented to incorporate and integrate the social and spatial dimensions within their respective theoretical paradigms. Likewise, the problem that these approaches have posed for the authors of both disciplines is approaching. Without pretending to be a clarifying and determining analysis on which current is the dominant one, the objective of this article is to present an exposition of the reflections that the various authors have developed when they have had to relate these two disciplines. As a fundamental contribution, the aim is to find their methodological space within each of them.